Pengaruh Penyempitan Penampang Krueng Pase terhadap Kedalaman Air Normal dan Kritis - Kurniati Kurniati; Irham Irham; Fauzi A. Gani; Fazlullah Fazlullah (Politeknik Negeri Lhokseumawe, 2022)
The Krueng Pase River is one of sources of raw water used for community needs.At this time The Krueng Pase River has undergone changes incross-sectional conditions, namely The occurrence of narrowing in several places. This cross-sectional change affects the flow pattern it passes through. Narrowing of the cross-sectional flow can cause changes in the river roughness coefficient Manning and also affect normal and critical flow conditions due to changes in flow velocity and cross-sectional area.Measurement using currentmeter and buoys for determining flow rate.the result is that there is a change in the slope to become more gentle whice causes a narrowing of the cross section due to reduced speed which affects the Manning value in the area (SoSc), steepflow.